Diseminasi Tugas Ombudsman Dalam Pencegahan Maladministrasi Dibidang Pendidikan - Firmansyah Putra; Helmi, Helmi; Hartati, Hartati; Dinda Syufradian Putra (Politeknik Piksi Ganesha Indonesia, 2025)
Maladministration practices in the world of education, especially at the high school level in Jambi Province. Maladministration in education refers to various forms of actions or policies that do not comply with ethical standards, laws, or good governance principles. Misuse of Education Funds that are not in accordance with their original purpose often occurs in education services which can cause legal violations and have criminal aspects. The purpose of this service is to provide an understanding of the role of the Ombudsman representative of Jambi Province to all stakeholders in the world of education, namely to prevent maladministration in education services, especially in high school to anticipate abuse of authority related to education funding which is feared to violate applicable laws and regulations. In this activity all Principals and Committees as well as from the media were invited to attend the Dissemination. All participants were involved in providing suggestions, input, and problems that have occurred so far. A joint commitment is needed in order to prevent illegal levies that often occur in the field of Upper Secondary Education in Jambi Province.